PERANCANGAN E-PROCUREMENT DINAS KOMUNIKASI DAN INFORMATIKA PEMERINTAH PROVINSI SUMATERA UTARA BERBASIS WEB - Samsudin, Samsudin; Fara Diva, Anggrayani (Jurnal Media Informatika, 2024)
The use of information system technology becomes very useful for companies that require accurate, reliable, fast, relevant and detailed information flow. Diskominfo Kota Medan is one of the implementing elements of the Medan City Government which is engaged in the field of Communication and Information, and has the task of carrying out household affairs in the field of Information and Communication and electronic data processing. In proposing the procurement of goods at Diskominfo Kota Medan, activities are still carried out manually, starting from recording the purchase of goods, stock, distribution, and budget management, making it possible that the process cannot be separated from errors in finding the necessary data. By making this web-based e-procurement information system, it is hoped that it will facilitate existing problems and be better in time efficiency, transparency, including in searching for the necessary data. This information system is designed with the FAST (Framework for the Application System Thinking) development method which consists of problem scope, problem analysis, requirements analysis, logical design and physical design. The design of this information system uses the PHP Programming language, HTML, and MySQL as its storage database.